Un-Healthy Marital Interactions: What Not To Do and What Can Be Done! FCS2247/FY847, 8/2006 - Baugh, Eboni J. (EDIS, 2006)
FCS-2247, a 3-page fact sheet by Eboni J. Baugh, takes a different approach to relationship advice by focusing on four negative patterns of interaction which have been demonstrated to be major destroyers of marital relationships: criticism, contempt, defensiveness, and stonewalling. She then provides several suggestions for ways to break these patterns. Includes references. Published by the UF Department of Family Youth and Community Sciences, August 2006.